Evaluation of Speech, Spatial Perception and Hearing Quality in Unilateral, Bimodal and Bilateral Cochlear Implant Users - ÇİPRUT, AYŞE AYÇA (GALENOS YAYINCILIK, 2019)
Objective: The aim of the study was to conduct a scale-based evaluation of the hearing skills of unilateral, bimodal and bilateral cochlear implant (CI) users, including distinguishing, orientating and locating speech and environmental sounds in their surrounding environment that they are exposed to in different contexts of everyday life. The scale results were compared between groups. Methods: A total of 74 cochlear implant users, 30 unilateral, 30 bimodal and 14 bilateral, were included in the study. Their ages ranged from 11 to 64 years. Participants were assessed using the Speech, Spatial and Qualities of Hearing Scale (SSQ). Results: Bilateral CI users' subjective ratings of their own hearing skills were found to be significantly better than those of bimodal and unilateral CI users; bimodal users' subjective ratings were also found to be significantly better than those of unilateral Cl users. Paired comparisons showed statistically significant differences between the groups in terms of total scores of Speech, Spatial, Qualities of Hearing and General SSQ(p<0.05). Conclusion: Our findings show that bilateral use of cochlear implants should be recommended for those presently using bimodal and unilateral devices. Moreover, subjective tests should be used regularly along with objective tests for evaluating CI patients.
Keywords: Cochlear implant; speech perception; spatial hearing; hearing quality; ADULTS; LOCALIZATION; INTELLIGIBILITY; BENEFITS; NOISE